1989
DOI: 10.1002/j.1537-2197.1989.tb11352.x
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Animal‐plant Interaction: Feeding of Schomburgkia Tibicinis (Orchidaceae) by Ants

Abstract: The hollow pseudobulbs of Schomburgkia tibicinis (Orchidaceae; Central America) serve as domatia for many species of ants. The ants pack many of the pseudobulbs with debris including dead insects, plant material, and sand. Ants were fed 14C‐labelled D‐glucose in honey, killed, and placed in the pseudobulbs for up to eight weeks. Samples of plant tissue were harvested and tested for radioactivity after 1, 2, 3, 4, 6, and 8 weeks. The labelled material had moved into various parts of the plant and demonstrated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 8 publications
0
22
0
1
Order By: Relevance
“…As a result, it has long been supposed that the plants also benefit from nutrients originating from ant waste based on the fact that colonies concentrate nutrients for the plants when they install themselves at the base of FB-or EFN-bearing plants (Wagner, 1997; see also Heil et al ., 2001b). This trait has major importance for many myrmecophytic epiphytes that obtain nutrients from ant waste deposited in their absorptive chambers (Benzing, 1970;Janzen, 1974;Huxley, 1978;Rickson, 1979;Rico-Gray et al ., 1989;Treseder, Davidson & Ehleringer, 1995). Evidence of this type of mutualistic interaction, so-called myrmecotrophy (see Beattie, 1989;Benzing, 1991), has also been noted for myrmecophytic geophytes such as Malaysian rattan palms (Rickson & Rickson, 1986) and Neotropical Cecropia (Sagers, Ginger & Evans, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it has long been supposed that the plants also benefit from nutrients originating from ant waste based on the fact that colonies concentrate nutrients for the plants when they install themselves at the base of FB-or EFN-bearing plants (Wagner, 1997; see also Heil et al ., 2001b). This trait has major importance for many myrmecophytic epiphytes that obtain nutrients from ant waste deposited in their absorptive chambers (Benzing, 1970;Janzen, 1974;Huxley, 1978;Rickson, 1979;Rico-Gray et al ., 1989;Treseder, Davidson & Ehleringer, 1995). Evidence of this type of mutualistic interaction, so-called myrmecotrophy (see Beattie, 1989;Benzing, 1991), has also been noted for myrmecophytic geophytes such as Malaysian rattan palms (Rickson & Rickson, 1986) and Neotropical Cecropia (Sagers, Ginger & Evans, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In Australasia, the majority of ant-plants are epiphytes and appear to be primarily involved in trophic mutualisms rather than defense mutualisms (22,24). An epiphytic habit means uneven water and nutrient supplies (26), and mutualisms with plant-nesting ants that provide detritus and feces to their host (27)(28)(29)(30)(31)(32)(33)(34) are thus common among epiphytes (22). These mutualistic symbioses range from facultative interactions involving many arboreal ant species to obligate interactions that can be species-specific (17,28,32,34,35).…”
mentioning
confidence: 99%
“…By tracing radioactive or stable isotope‐labelled substances, numerous studies have found evidence of nutrient absorption from ant nests to plant tissues (Rico‐Gray et al . ; Treseder, Davidson & Ehleringer ; Sagers, Ginger & Evans ; Sternberg et al . ; Farji‐Brener & Ghermandi ; Wagner & Nicklen ; Lescano et al .…”
Section: Discussionmentioning
confidence: 99%